2002
DOI: 10.1002/sia.1411
|View full text |Cite
|
Sign up to set email alerts
|

Infrared reflection investigation of ion‐implanted and post‐implantation‐annealed epitaxially grown 6H‐SiC

Abstract: Multiple energy Al+ and C + ions were implanted into 6H-SiC at room temperature (25 • C) and elevated temperature (600 • C), respectively, followed by 1550• C annealing for 30 min. Fourier transform infrared spectroscopy was used to evaluate the optical properties in the mid-infrared range. An effective medium model, taking into account the presence of an implantation-induced amorphous phase, was developed to establish the relationship between the changes of optical properties and modification of structure.Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It was reported [22] that the reflectance at the top of the reststrahlen band is sensitive to the surface condition of the SiC material/film and that a rough surface could cause the reflectance to drop from the low frequency edge to the high frequency edge. We have performed a theoretical calculation on the infrared (IR) reflectance spectra of 6H-SiC based upon the effective medium model [23]. It was indicated that the amorphization of the implanted layer is responsible for the presence of the deep reflection dip at ∼930 cm − 1 , which is exactly seen from Fig.…”
Section: Raman Scattering Under Uv 325 Nm Excitationmentioning
confidence: 80%
“…It was reported [22] that the reflectance at the top of the reststrahlen band is sensitive to the surface condition of the SiC material/film and that a rough surface could cause the reflectance to drop from the low frequency edge to the high frequency edge. We have performed a theoretical calculation on the infrared (IR) reflectance spectra of 6H-SiC based upon the effective medium model [23]. It was indicated that the amorphization of the implanted layer is responsible for the presence of the deep reflection dip at ∼930 cm − 1 , which is exactly seen from Fig.…”
Section: Raman Scattering Under Uv 325 Nm Excitationmentioning
confidence: 80%
“…10(a)), it is clear that the characteristic SiC Raman peaks (between 750 and 1000 cm -1 ) disappeared and three broad Raman bands appeared around 519, 880 and 1424 cm -1 . These broad bands are caused by the vibrations of Si-Si, Si-C and C-C bonds, respectively [19]. This change in the spectrum indicates that the SiC layer is amorphized as a result of the implantation.…”
Section: Raman Resultsmentioning
confidence: 98%
“…Recently, it has been reported that the crystalline damage induced by ion implantation affects the infrared (IR) reflectance spectra around the reststrahlen region (~800-1000 cm -1 ) [33,34], and the difference of carrier concentration between epitaxial layer and substrate induces the interference oscillation in the near IR region (1000-4500 cm -1 ). In this study, we performed the IR reflectance measurements in the spectral range between 600 and 8000 cm -1 for high-dose phosphorus ion implanted and post-implantation-annealed 4H-SiC wafers to characterize both the electrical properties and crystalline damage of the implanted layers without destruction and contactless.…”
Section: Characterization Of Electrical Properties and Residual Crystmentioning
confidence: 99%
“…We analyzed the observed spectra to evaluate the damage of the ion implantation layers assuming that the implanted layers are composed of two phases, recrystallized SiC phase and defective SiC phase. We have derived the effective dielectric constants ε eff of implanted layers using an effective medium approximation (EMA) [33], where ε c and ε d are the dielectric constants of re-crystallized and damaged phases, respectively, and f is the volume fraction of damaged phase. We assumed that the frequency dependence of both the dielectric constants of re-crystallized phase and defective phase follows the MDF model given by eq.(1).…”
Section: High-dose Phosphorus Ion Implantation Post-implantation Annmentioning
confidence: 99%